Comparative Analysis of Endowment Life Insurance Premium Reserves Using the Canadian Method Based on the 2019 TMI and Gompertz’s Law - Riaman; Sukono; Irene Araminta Febry (Rescollacom (Research Collaborations Community), 2026)
Life uncertainty, particularly mortality risk, creates the need for financial protection through life insurance. Endowment life insurance is a product that provides both death benefits and survival benefits at the end of the coverage period; therefore, insurance companies must establish adequate premium reserves. This study aims to calculate premium reserves for endowment life insurance using the Canadian method and to compare the effects of different mortality models based on the 2019 Indonesian Mortality Table (TMI) and Gompertz’s law. The results show that premium reserves calculated using Gompertz’s law are higher than those calculated using the 2019 Indonesian Mortality Table (TMI). This difference indicates that the choice of mortality model affects the magnitude of the resulting premium reserves.